2012
DOI: 10.1115/1.4005698
|View full text |Cite
|
Sign up to set email alerts
|

Second Law Assessment of a Wet Ethanol Fuelled HCCI Engine Combined With Organic Rankine Cycle

Abstract: In this study, first and second law analyses of a new combined power cycle based on wet ethanol fuelled homogeneous charge compression ignition (HCCI) engine and an organic Rankine cycle are presented. A computational analysis is performed to evaluate first and second law efficiencies, with the latter providing good guidance for performance improvement. The effect of changing turbocharger pressure ratio, organic Rankine cycle (ORC) evaporator pinch point temperature, turbocharger compressor efficiency, and amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…ethanol (bio-ethanol) in HCCI engine and its analysis via exergy method. Equations used for evaluating performance parameters have been referred from Trivedi, Khaliq, and Sharma (2010), Khaliq, Trivedi, and Dincer (2011), and Khaliq and Trivedi (2012). These equations are applied according to sub-system's operational and boundary conditions.…”
Section: Discussion On Results Obtainedmentioning
confidence: 99%
See 3 more Smart Citations
“…ethanol (bio-ethanol) in HCCI engine and its analysis via exergy method. Equations used for evaluating performance parameters have been referred from Trivedi, Khaliq, and Sharma (2010), Khaliq, Trivedi, and Dincer (2011), and Khaliq and Trivedi (2012). These equations are applied according to sub-system's operational and boundary conditions.…”
Section: Discussion On Results Obtainedmentioning
confidence: 99%
“…It is observed that combined cycle has improved thermal and exergy efficiencies by recovering some of the thermal energy of the exhaust gases to develop more efficient and environment friendly engine thus utilising waste exergy and reducing thermal pollution. The papers Khaliq, Trivedi, and Dincer (2011) and Khaliq and Trivedi (2012) deal with the study of HCCI engine performance based on ambient temperature variation (T 0 ), pressure ratio (Pr), turbocharger compressor efficiency (η c ) and pinch point on the system performance. However in the present paper, the work has been extended further to evaluate the performance of HCCI engine on the basis of variation of effectiveness of regenerator.…”
Section: Second Law Analysis Of Alternative Fuelled Engine and Researmentioning
confidence: 99%
See 2 more Smart Citations
“…Exergy analysis has been applied to spark ignited and diesel engines in several prior studies [1][2][3] to explore the interaction of loss mechanisms with different engine design and operating parameters. In an HCCI context, exergy analysis has been applied in prior studies [3][4][5] as well, however many of these prior studies significantly simplify the in-cylinder processes and approximate Contributed by the Cotnbustion and Fuels Committee of ASME for publication in the JOURNAL OF ENGINEERING FOR GAS TURBINES AND POWER. Manuscript received April 14,2013; final manuscript received May 16, 2013; pubhshed online July 31, 2013.…”
Section: Introductionmentioning
confidence: 99%